2022
DOI: 10.3389/fpsyg.2022.954828
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of innovation capability and social adaptability on undergraduates’ employability: The role of self-efficacy

Abstract: Introduction: As the world is consistently driven by the infusion of new-generation information technology and the knowledge economy, college students are placed under mounting pressure in developing occupation-related competencies. Their employability has been receiving growing concerns from stakeholders such as higher education institutions, governments, employers, parents, and even student groups themselves as it plays a decisive role in occupational success, social stability, and economic prosperity. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 153 publications
1
4
0
Order By: Relevance
“…The results showed that those in the high level group had higher scores for personal factors, social environment, family and friends, school, and professional issues, suggesting that employment stress among rural college students is the result of a combination of factors. This result is consistent with the findings of Li et al (2022) , whose study showed that personal and professional factors are related to students’ personal evaluations and employment expectations, and that low personal evaluations and high employment expectations often lead to a loss of individual self-confidence in employment and a sudden increase in employment pressure. In addition, according to the stimulus-physiological/psychological-response (SOR) theoretical model, external factors can produce a direct psychological response in the body: when the employment social environment the is highly competitive, there are too few jobs, and the school’s previous students have poor employment records, it will increase the individual’s employment panic ( Ardern et al, 2012 ; Anselme and Güntürkün, 2019 ; Mladenović et al, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results showed that those in the high level group had higher scores for personal factors, social environment, family and friends, school, and professional issues, suggesting that employment stress among rural college students is the result of a combination of factors. This result is consistent with the findings of Li et al (2022) , whose study showed that personal and professional factors are related to students’ personal evaluations and employment expectations, and that low personal evaluations and high employment expectations often lead to a loss of individual self-confidence in employment and a sudden increase in employment pressure. In addition, according to the stimulus-physiological/psychological-response (SOR) theoretical model, external factors can produce a direct psychological response in the body: when the employment social environment the is highly competitive, there are too few jobs, and the school’s previous students have poor employment records, it will increase the individual’s employment panic ( Ardern et al, 2012 ; Anselme and Güntürkün, 2019 ; Mladenović et al, 2023 ).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that employment stress includes many aspects such as personal factors, social environment, family and friends, school, and professional issues, and that rural college students have different characteristics of employment stress when they face different employment dilemmas ( Szromek and Wolniak, 2020 ; Kossek et al, 2021 ; Ojo et al, 2021 ; Rawal, 2023 ). According to the characteristics of the employment pressure on rural college students, formulating individualized employment guidance and support will help adjust their employment psychology and employment outlook, and effectively help rural college students achieve successful employment ( Li et al, 2022 ). Previous studies showed that rural college students with the same employment psychology presented different employment stress characteristics ( Belle et al, 2022 ; von Keyserlingk et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…A strong belief in one's capacity to apply information and abilities is a sign of high self-efficacy, and this belief is a crucial factor in determining success in the job. Graduates that possess high self-efficacy are more likely to be innovative, proactive, and problem-solvers, which increases job satisfaction and opens up professional progression prospects (Li et al, 2022). This combination benefits individual career trajectories and the competitiveness of organisations by fostering a culture of innovation and continual learning.…”
Section: The Suitability Of Study Programs For Careersmentioning
confidence: 99%
“…On the whole, there are various reasons for students' employment psychological problems in higher vocational colleges, which may be the result of the interaction of internal, external, personal or social factors. Therefore, solving these problems requires the joint efforts of schools, families and society, providing more comprehensive support and help, guiding students to establish a correct concept of employment, making career plans, enhancing self-confidence and enhancing employment competitiveness, so as to better adapt to employment challenges [6].…”
Section: Lack Of Academic Performance and Practical Experiencementioning
confidence: 99%